CURRENT PROBLEMS OF APPLYING A BLOOD-BACK TOUR IN ARTERIAL BLEEDING FROM THE UPPER EXTREMITY (Physical Culture and Sport: Scientific Perspective, 2022)
Arterial bleeding from the upper limb occurs in various pathological conditions, but first of all in traumas - wounds, open fractures, amputations. In the scientific and educational literature, the imposition of a tourniquet on the upper limb is usually reported with general concepts, namely, that the tourniquet is placed on the lower and upper third of the shoulder and on the axilla, without argumentation - in which clinical situation it is necessary to apply it to that particular or another area, and when not to apply at all.When conducting practical classes with future rehabilitators, paramedics, and nurses, we encountered a situation where students apply a tourniquet at their own discretion, regardless of the clinical situation.Stopping arterial bleeding, like any other medical manipulation, should be individual. The main measure of effective care should be not only the fact of saving the patient's life and delivering him to a medical institution, but also taking into account the prospects of further radical treatment. It is the adequate stopping of bleeding in a specific clinical situation with the least ischemia of the damaged limb that will be a measure of the professional skill of the medical worker.After the introduction into the educational process of the clear instructions developed by us regarding the levels of regional application of hemostatic tourniquets, students clearly understood the problem and began to perform tasks according to clinical data.
Keywords: arterial bleeding; arterial tourniquet; algorithm